Estudios citogenéticos en niños con Leucemia Linfocitica Aguda-B en Costa Rica - Venegas, Patricia (2004)
Cytogenetic studies in children with Acute Lymphocytic Leukemia-B in Costa Rica. Chromosome analyses were performed on bone marrow of 177 pediatric patients with Acute Lymphocytic Leukemia at the “Hospital Nacional de Niños”. The standard cytogenetic techniques now belongs to the panel of mandatory analyses performed at diagnosis of our acute leukemia patients and represent a major advantage to be effective and independent prognostic factors, essential for therapeutic choices. Cytogenetic results were achieved in 83% of the bone marrow samples: normal karyotypes represented 29% and abnormal karyotypes 71% with the follow distribution: t(9;22) 3%; t(1;19) 5%; t(4;11) 3%, Hyperdiploidy 39%; other chromosomal abnormalities 21%. Systematic cytogenetic analyses are essential to define morpho-immunologic sub-types of leukemia and to detect new translocations that allows to understand hematopoiesis and leukemogenesis. Rev. Biol. Trop. 52(3): 551-558. Epub 2004 Dic 15